Are Allogeneic Blood Transfusions Associated With Decreased Survival After Surgery for Long-bone Metastatic Fractures? - Janssen, Stein J. (Clin Orthop Relat Res, 2015)
BACKGROUND: Previous studies have shown that perioperative blood transfusion increases cancer recurrence and decreases patient survival after resection of primary malignancies. The question arises whether this association also exists in patients with already disseminated disease undergoing surgery for metastatic long-bone fractures. PURPOSES: We sought to determine whether perioperative allogeneic blood transfusion is associated with decreased survival after operative treatment of long-bone metastatic fractures after accounting for clinical, laboratory, and treatment factors. Secondarily, we aimed to identify potential factors that are associated with decreased survival. METHODS: We included 789 patients in our retrospective study who underwent surgery at two institutions for a pathologic or impending metastatic long-bone fracture. We used multivariable Cox proportional hazards regression model analysis to assess the relationship of perioperative allogeneic blood transfusion with survival, and accounted for patient age, sex, comorbidities, BMI, tumor type, fracture type and location, presence of other bone and visceral metastases, previous radiotherapy and systemic therapy, preoperative embolization, preoperative hemoglobin level, treatment type, anesthesia time, blood loss, duration of hospital admission, year of surgery, and hospital. RESULTS: Considering transfusion as an “exposure,” and comparing patients who received transfusions with those who did not, we found that blood transfusion was not associated with decreased survival after accounting for all explanatory variables (hazard ratio [HR] 1.06; 95% CI, 0.87–1.30; p = 0.57). Evaluating transfusion in terms of dose-response, we found that patients who received more transfusions had lower survival compared with those who had fewer transfusions after accounting for all explanatory variables (HR per unit of blood transfused, 1.07; 95% CI, 1.02–1.12; p = 0.005). We found that age (HR, 1.02; 95% CI, 1.01–1.02; p < 0.001), comorbidity status (HR, 1.06; 95% CI, 1.01–1.10; p = 0.014), duration of hospital stay (HR, 1.02; 95% CI 1.00–1.03; p = 0.021), tumor type (HR, 1.71; 95% CI, 1.44–2.03; p < 0.001), and visceral metastases (HR, 1.59; 95% CI, 1.34–1.88; p < 0.001) were independently associated with survival. CONCLUSION: We found that exposure to perioperative allogeneic blood transfusion does not decrease survival, with the numbers available. However, our sample size might have been insufficient to reveal a small but potentially relevant effect. Our results do suggest a dose-response relationship; patients who received more transfusions had lower survival compared with those with fewer transfusions. Risk of death increased by 7% per unit of blood transfused. LEVEL OF EVIDENCE: Level III, prognostic study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-015-4167-3) contains supplementary material, which is available to authorized users.